The Sensitivity of Amphotericin B, Fluconazole, and Flusitosin to Fungal Pathogens Isolated from Wounds of Diabetic Ulcer Patients - Sari, Rafika (Brawijaya University, 2022)
A diabetic ulcer is a wound caused by infection, ulceration or destruction in people with diabetes mellitus. Mostly, diabetic ulcer found in foot. The purpose of this study was to identify pathogenic fungi in diabetic ulcers and their sensitivity to fungal drugs. The morphological determination of fungal isolates was stained with Lactophenol Cotton Blue. Determination of sensitivity using diffusion discs Kirby Bauer which are classified based on Clinical Laboratory Standard Institute (CLSI) with Amphotericin B, Fluconazole, and Flusitosin. Based on the results of the study found 8 types of pathogenic fungi namely Candida albicans (38.78%), Candida guilliermondii (4.08%), Candida kefyr 10.20%), Candida parapsilosis (10.20%), Fusarium solani (14.29) %), Microsporum audouinii (14.29%), Penicillium sp(2.04%), Trichophyton mentagrophytes (4.08%), and Trichophyton equinum (2.04%). The fungus was identified using Gideon software and the book Description of Medical Fungi. The results of the antifungal sensitivity test showed the results were sensitive to fluconazole. Amphotericin B is intermediate to Candida albicans, Candida guilliermondii, Penicillium sp. and Trichophyton sp. and is resistant to Candida kefyr and Candida parapsilosis. Flusitosin is only an intermediate against Penicillium sp. while other fungal species are immune. The conclusion of this study. The results of diabetic ulcer swabs III and IV indicate the presence of fungal colonies with species of 9 species namely Candida albicans, Candida guilliermondii, Candida kefyr, Candida Parapsilosis, Fusarium solani, Microsporum Audouinii, Penicillium sp., Trichophyton mentagrophytes, and Trichophyton equinum. Antifungal sensitivity tests on all pathogenic fungi showed sensitivity to fluconazole. Amphotericin Bintermediatrics against Candida albicans, Candida guilliermondii, Penicillium sp. and Trichophyton sp. while resistant to Candida kefyrand Candida parapsilosis. Flusitosin is only an intermediate against Penicillium sp. while other fungal species are resistant.